Influence of External Pressure on the Performance of Quantum Dot Solar Cells - Kim, Jaehoon; Jeong, Byeong Guk; Roh, Heebum; Song, Jiyun; Park, Myeongjin; Lee, Doh C.; Bae, Wan Ki; Lee, Changhee (American Chemical Society, 2016)
We report the influence of post-treatment via the external pressure on the device performance of quantum dot (QD) solar cells. The structural: analysis together with optical and electrical characterization on QD solids reveal that the external,pressure compacts QD active layers by removing the mesoscopic voids and enhances the charge carrier transport-along QD solids leading to significant increase in J(SC) of QD solar cells. Increasing the external pressure, by contrast, accompanies reduction in FE and V-OC, yielding the trade-off relationship among J(SC), and FF and V-OC in PCE of devices. Optimization at the external pressure in the present study at 1.4-1.6 MPa enables us to achieve over 10% increase in PCE of QD solar cells. The approach and results show that the control over the organization of QDs is the key for the-charge transport properties in ensemble and also offer simple yet effective; mean to enhance the electrical performance of transistors and solar cells using QDs.
Keywords: PHOTOVOLTAICS; NANOPARTICLES; STRATEGIES; EFFICIENCY; SOLIDS; ARRAYS